Fundamentos Básicos de la Natación y su Erradicación de la Inhibición Motriz en Niños. - Veloz Carvajal, Lilian Jacqueline (2025)
This research aimed to determine whether teaching the basic fundamentals of swimming can help reduce motor inhibition in 12-year-old children from the "Nuestro Mundo Eco Río" Educational Unit. An experimental group of 8 students was selected and subjected to pre- and post-tests around an intervention based on aquatic activities. Two main tools were used: The Test for Control and Monitoring of Aquatic Activity by Moreno and Gutiérrez (1994), which enabled the observation of clear improvements in basic water skills, and the Motor Test SportComp RICYDE, which evaluates various aspects of motor coordination through exercises such as: 7-meter two-footed run, 7-meter one-legged run, lateral jumps (9 seconds), and a 9-meter shuttle run. The data obtained were processed using Excel and analyzed with IBM SPSS Statistics software, applying appropriate statistical methods. The results show that the intervention had a positive impact on several of the assessed motor skills, suggesting that swimming can be an effective tool for enhancing motor development during this growth stage.